Quality of life and discriminating power of two questionnaires in fibromyalgia patients: fibromyalgia Impact Questionnaire and Medical Outcomes Study 36-Item Short-Form Health Survey - Assumpção,Ana (2010)
BACKGROUND: Fibromyalgia is a painful syndrome characterized by widespread chronic pain and associated symptoms with a negative impact on quality of life. OBJECTIVES: Considering the subjectivity of quality of life measurements, the aim of this study was to verify the discriminating power of two quality of life questionnaires in patients with fibromyalgia: the generic Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) and the specific Fibromyalgia Impact Questionnaire (FIQ). METHODS: A cross-sectional study was conducted on 150 participants divided into Fibromyalgia Group (FG) and Control Group (CG) (n=75 in each group). The participants were evaluated using the SF-36 and the FIQ. The data were analyzed by the Student t-test (α=0.05) and inferential analysis using the Receiver Operating Characteristics (ROC) Curve - sensitivity, specificity and area under the curve (AUC). The significance level was 0.05. RESULTS: The sample was similar for age (CG: 47.8±8.1; FG: 47.0±7.7 years). A significant difference was observed in quality of life assessment in all aspects of both questionnaires (p<0.05). Higher sensibility, specificity and AUC were obtained by the FIQ (96%, 96%, 0.985, respectively), followed by the SF-36 (88%, 89% and 0.948 AUC). CONCLUSION: The FIQ presented the highest sensibility, specificity and AUC showing the most discriminating power. However the SF-36 is also a good instrument to assess quality of life in fibromyalgia patients, and we suggest that both should be used in parallel because they evaluate relevant and complementary aspects of quality of life.